Internal financial constraints, external financial constraints, and investment choice: Evidence from a panel of UK firms - Guariglia, Alessandra (Journal of Banking & Finance, 2008)
This paper uses a panel of 24,184 UK firms over the period 1993–2003 to study the extent to which the sensitivity of investment to cash flow differs at firms facing different degrees of internal and external financial constraints. Our results suggest that when the sample is split on the basis of the level of internal funds available to the firms, the relationship between investment and cash flow is U-shaped. On the other hand, the sensitivity of investment to cash flow tends to increase monotonically with the degree of external financial constraints faced by firms. Combining the internal with the external financial constraints, we find that the dependence of investment on cash flow is strongest for those externally financially constrained firms that have a relatively high level of internal funds.